2013
DOI: 10.1007/s11255-013-0562-4
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TWEAK levels are independently associated with coronary artery disease severity in patients with stage 2–3 kidney disease

Abstract: Our results indicate a relationship between sTWEAK levels and CAD in CKD stages 2-3 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
5
0
5
Order By: Relevance
“…In the literature, there are contradictory findings of the relationship between TWEAK levels and atherosclerosis (27,28). Previous studies showed a negative relationship between serum TWEAK levels and coronary artery disease, cIMT, insulin resistance, gestational diabetes and type II diabetes (29)(30)(31)(32). However, studies cannot explain the reason why atherosclerotic process accelerated when serum TWEAK levels were low (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are contradictory findings of the relationship between TWEAK levels and atherosclerosis (27,28). Previous studies showed a negative relationship between serum TWEAK levels and coronary artery disease, cIMT, insulin resistance, gestational diabetes and type II diabetes (29)(30)(31)(32). However, studies cannot explain the reason why atherosclerotic process accelerated when serum TWEAK levels were low (33).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-like weak inducer of apoptosis (TWEAK) was recently found to stimulate the expression of inflammatory cytokines locally in kidney cells and to down-regulate the expression of Klotho in vitro and in vivo [11]. Soluble TWEAK levels were independently associated with coronary artery disease severity in patients with stage 2-3 CKD [12]. …”
Section: Outcomes Of Inflammation In Ckdmentioning
confidence: 99%
“…In addition to decreasing Klotho through epigenetic mechanisms, TWEAK directly promotes cardiac dysfunction and failure through downregulation of the mitochondrial biogenesis regulator PGC1α, an action of TWEAK that also contributes to CKD [52, 53], and increases vascular calcification [54]. In keeping with this, higher serum TWEAK levels are associated with the severity of coronary artery disease, particularly in CKD Stages 2 and 3 patients [55], and predict mortality in haemodialysis patients [56]. Liver TWEAK signalling is differentially activated by palm oil in association with insulin resistance [57] and in response to a high-fat diet, and it contributes to liver steatosis, fibrosis and inflammation and insulin resistance [58].…”
Section: Introductionmentioning
confidence: 99%